Rural areas as a prerequisite for the efficient use of the territories of mountainous regions (on the pattern of the Republic of Armenia) - Aksel' Arutyunovich Potosyan (Наука. Инновации. Технологии)
Scarcity of territorial resources in the Republic of Armenia forces more efficient and targeted usage of land. This is even more important taking into consideration complicated political and geographic position of the country. For the reason the prevailing part of the country and most of the settlements are located on altitudes higher than 1500 over sea level, relatively monotonic and stable resettlement and rational usage of natural resources are an urging problem. The article is stating the point of view that effectiveness of use of land and territory resources in mountainous countries at all and particularly in Armenia directly correlates with the density and level of population, statement is based on analysis and summarizing of actual and statistical material. Development of rural areas and resettlement, agglomeration of medium and small villages, preserving existing network of settlements as well as reconstruction and repopulation of abandoned ones is one of the most important objectives of social-economic development of country.